Surface Modification and Enhancement of Ferromagnetism in BiFeO3 Nanofilms Deposited on HOPG - Shikhgasan Ramazanov; Dinara Sobola; Farid Orudzhev; Alexandr Knápek; Josef Polčák; Michal Potoček; Pavel Kaspar; Rashid Dallaev (Nanomaterials, 2020)
BiFeO3 (BFO) films on highly oriented pyrolytic graphite (HOPG) substrate were obtained by the atomic layer deposition (ALD) method. The oxidation of HOPG leads to the formation of bubble regions creating defective regions with active centers. Chemisorption occurs at these active sites in ALD. Additionally, carbon interacts with ozone and releases carbon oxides (CO, CO2). Further annealing during the in situ XPS process up to a temperature of 923 K showed a redox reaction and the formation of oxygen vacancies (Vo) in the BFO crystal lattice. Bubble delamination creates flakes of BiFeO3-x/rGO heterostructures. Magnetic measurements (M–H) showed ferromagnetism (FM) at room temperature Ms ~ 120 emu/cm3. The contribution to magnetization is influenced by the factor of charge redistribution on Vo causing the distortion of the lattice as well as by the superstructure formed at the boundary of two phases, which causes strong hybridization due to the superexchange interaction of the BFO film with the FM sublattice of the interface region. The development of a method for obtaining multiferroic structures with high FM values (at room temperature) is promising for magnetically controlled applications.